The Role of Trust as a Mediator in Enhancing Purchase Decisions for iPhone - Prastowo, Sugeng Lubar; Sobirov, Bobur; Alunis, Kalyca Shafhah Suci; Az-Zahra, Aulia Miftah; Syahira, Aurisa (International Journal of Business, Law, and Education, 2024)
This study aims to examine the influence of brand image, product quality, and lifestyle on iPhone purchase decisions in Tangerang, with trust as a mediating variable. The study is motivated by the significant increase in iPhone usage in Indonesia, despite a decline in sales observed in 2023. The sample consists of 180 iPhone users selected through non-probability sampling. Data were collected using Likert-scale questionnaires and analyzed using the SEM approach with SmartPLS 3.0. The results show that brand image, lifestyle, and trust significantly influence purchase decisions, while product quality requires trust mediation to impact purchase decisions. These findings emphasize the importance of integrating trust into marketing strategies to enhance purchase decisions.